Expression of a grape (Vitis vinifera) bZIP transcription factor, VlbZIP36, in Arabidopsis thaliana confers tolerance of drought stress during seed germination and seedling establishment. (November 2016) - Tu, Mingxing; Wang, Xianhang; Feng, Tongying; Sun, Xiaomeng; Wang, Yaqiong; Huang, Li; Gao, Min; Wang, Yuejin; Wang, Xiping
Highlights: VlbZIP36 is involved in response to drought and ABA in grape. Ectopic expression of VlbZIP36 in A. thaliana enhanced dehydration tolerance during the seed germination, seedling and mature plant stages. VlbZIP36 plays a role in drought tolerance by improving the water status, through limiting water loss and mitigating cellular damage. VlbZIP36 promotes the ABA dependent signal transduction. Abstract: Drought is one of the most serious factors that limit agricultural productivity and there is considerable interest in understanding the molecular bases of drought responses and their regulation. While numbers of basic leucine zipper (bZIP) transcription factors (TFs) are known to play key roles in response of plants to various abiotic stresses, only a few group K bZIP TFs have been functionally characterized in the context of stress signaling. In this study, we characterized the expression of the grape ( Vitis vinifera ) group K bZIP gene, VlbZIP36, and found evidence for its involvement in response to drought and the stress-associated phytohormone abscisic acid (ABA). Transgenic Arabidopsis thaliana lines over-expressing VlbZIP36 under the control of a constitutive promoter showed enhanced dehydration tolerance during the seed germination stage, as well as in the seedling and mature plant stages. The results indicated that VlbZIP36 plays a role in drought tolerance by improving the water status, through limiting water loss, and mitigating cellular damage. The latter was evidenced by reduced cell death, lower electrolyte leakage in the transgenic plants, as well as by increased activities of antioxidant enzymes. We concluded that VlbZIP36 enhances drought tolerance through the transcriptional regulation of ABA-/stress-related genes.